2015
DOI: 10.1155/2016/5646384
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stromal Cells from Different Sources Diverge in Their Expression of Cell Surface Proteins and Display Distinct Differentiation Patterns

Abstract: When germ-free cell cultures became a laboratory routine, hopes were high for using this novel technology for treatment of diseases or replacement of cells in patients suffering from injury, inflammation, or cancer or even refreshing cells in the elderly. Today, more than 50 years after the first successful bone marrow transplantation, clinical application of hematopoietic stem cells is a routine procedure, saving the lives of many every day. However, transplanting other than hematopoietic stem and progenitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 71 publications
2
124
0
5
Order By: Relevance
“…However, hematopoietic cell markers (such as CD45, CD34 and CD19) were not expressed. All the surface markers expression detected in the three tissues-derived MSCs conformed to the criteria of MSCs established before 19 and no comparable differences were observed among UC-MSC, Ad-MSC and BM-MSC.
Figure 2Immunophenotype of MSCs. UC-MSC ( A ), Ad-MSC ( B ) and BM-MSC ( C ) were labeled with antibodies against the indicated antigens, and analyzed by flow cytometry.
…”
Section: Resultsmentioning
confidence: 77%
“…However, hematopoietic cell markers (such as CD45, CD34 and CD19) were not expressed. All the surface markers expression detected in the three tissues-derived MSCs conformed to the criteria of MSCs established before 19 and no comparable differences were observed among UC-MSC, Ad-MSC and BM-MSC.
Figure 2Immunophenotype of MSCs. UC-MSC ( A ), Ad-MSC ( B ) and BM-MSC ( C ) were labeled with antibodies against the indicated antigens, and analyzed by flow cytometry.
…”
Section: Resultsmentioning
confidence: 77%
“…Among these, mesenchymal stem/stromal cells (MSCs) have been the most abundantly used. MSCs have multi‐lineage differentiation potential and can be isolated from various tissue sources including bone marrow, adipose tissue, and umbilical cord . In addition to their osteogenic, chondrogenic, and adipogenic differentiation potential, MSCs can orchestrate the function of other cells by paracrine signalling or even endocrine mechanisms .…”
Section: Advances In Treatment Of Local Muscle Injuriesmentioning
confidence: 99%
“…Thereafter, a large number of studies correlated MSC phenotypic features and investigated the therapeutic potential of MSCs. Elahi et al reported that the term "mesenchymal stem cell" yielded more than 357,000 hits in Google Scholar (Google Scholar; July 2015) [30]. Colonyforming cells have since been called "mesenchymal stem cells" or "mesenchymal stromal cells."…”
Section: Mscs Are Defined As Self-renewing Populations In Multiple Ormentioning
confidence: 99%
“…Interestingly, "stemness" has been shown to be a stricter term for MSCs involved in tissue repair (Fig. 2) [30]. Recently, "skeletal stem cells (SSCs)" has supplanted the term "tissue stem cells" as the new term for these cells [31,32].…”
Section: Mscs Are Defined As Self-renewing Populations In Multiple Ormentioning
confidence: 99%